Exploring Paradiplomacy in Cybersecurity: A Case Study on Cyber Defense Academy in Singhasari Special Economic Zone - Safira, Putri Alyaa; Diphda, Bintang Corvi; Hannun, Syaharanie Mulya (Journal of Paradiplomacy and City Networks, 2025)
Various studies on paradiplomacy have been conducted in Indonesia. However, only a few have addressed the advancement of cybersecurity within the paradiplomacy framework. Therefore, this study explored the paradiplomacy in the cybersecurity sector, using the Cyber Defense Academy (CDA) in the Singhasari Special Economic Zone (SEZ) as a case study. This research employed a descriptive qualitative method through document analysis, interview data with a CDA representative, and secondary literature. The findings indicated that through collaboration with sub-national partners from India, such as Diaas.in and Aquarii India, the CDA represented a new model of paradiplomatic governance under the coordination of the Singhasari SEZ. This study concluded that the CDA denoted a new form of paradiplomacy with the potential to strengthen Indonesia’s cybersecurity network and emerged as a distinct type of actor within the paradiplomatic landscape.